Acquiring Interactional Competence in A Socially Constructed Environment Through the Use Of "Roll N' Play": An Interactional Board Game / Salina Sabri ... [et al.] - Sabri, Salina; Khairuddin, Zulaikha; Amir Johan, Syafiqah Johan; Mohd Daud, Khairunnisa (Universiti Teknologi MARA, 2020)
This paper highlights the benefits of game-based learning for adults in acquiring interactional competence in English. Roll N' Play is an interactional board game that is deemed to be an appropriate learning tool for acquiring interactional competence in English for adults because in acquiring a language, it has to be of use in any adult's professional and personal lives. Roll N' Play enables players to use English, the target language, in a socially constructed environment while having fun in a competitive environment and at the same time applying peer-learning strategies. Roll N' Play allows a hands-on experience in language use and it also fosters creativity and problem-solving skills as players compete to reach the highest score in order to win the game. This board game has four bonus squares, eight challenge squares, two penalty squares and one first date square. The educational benefit of this innovation is that it will inevitably improve players' interaction competence because players are required to interact with other players to complete situational-based tasks in a timely manner. Although there are many online language games and applications, those who are not Internet- savvy will not be able to enjoy such games applications and some users may even find them unappealing. This paper concludes that purposeful language use can be promoted through an engaging and enjoyable social activity such as a board game.